If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -6) = -49 Reorder the terms: 2(-6 + 3x) = -49 (-6 * 2 + 3x * 2) = -49 (-12 + 6x) = -49 Solving -12 + 6x = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = -49 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = -49 + 12 6x = -49 + 12 Combine like terms: -49 + 12 = -37 6x = -37 Divide each side by '6'. x = -6.166666667 Simplifying x = -6.166666667
| 13h-11h=10 | | y=-1+2 | | 4(3x+7)=5(2x-6) | | -19z+7z+6=-18 | | -1/3u=10 | | 1-m/1+m=2/3 | | 6=10(x-10)+4-8x | | -1/5p=-16 | | -15d-16d+20d=-11 | | b-0.73=1.9 | | -5x-5(-2x-13)=40 | | 2=-1/13a | | 41/2s=-30 | | 7/10+2d/3 | | 18t-17t=18 | | 7y+-3(y+6)=10 | | 3x-2=1/2 | | x^2+22x+59= | | -7c-13c+18c+5c=15 | | 9.36k-2.012=8.89k | | (7)/(8)*-(9)/(10)=-(1)/(8) | | a+3.4=-1.28 | | 5x+48=8x | | 1.3/4=x/9 | | 7x^2=20 | | -6x+6=4 | | -12k+-4k+10k+3k-6k=-18 | | -52=3+5x | | p+496=500 | | 35x-36=5 | | 4x+11=-17 | | -20=-5/8x |